PENGABDIAN PARTISIPATIF MASYARAKAT DALAM PENGEMBANGAN IDE UMKM KREATIF DAN INOVATIF DI TENGAH PENDEMI COVID 19 DI DESA PIKAT KABUPATEN KLUNGKUNG - Putu Eka Purnamaningsih; Kadek Wiwin Dwi Wismayanti; Ni Wayan Ari Sudiartini (JURNAL SEWAKA BHAKTI, 2021)
In the midst of the Covid-19 pandemic, economic improvements must be made by all levels of society so that they can meet their daily needs. One way to improve the community's economy can be done by increasing the UMKM (Micro, Small and Medium Enterprises). UMKM (Micro, Small and Medium Enterprises) actors are slowly starting to experience problems arising from the pandemic such as marketing and capitalization. In accordance with the objective desired by the researcher, namely the formation of community participation in increasing creative and innovative MSMEs in Pikat Village, Dawan District, Klungkung Regency. Having creative and innovative ideas about MSMEs in the midst of a pandemic like this can help people to survive in their current conditions. Currently, MSMEs in Indonesia continue to experience a drastic decline. Not a few MSMEs have to go out of business because of the lack of customers, so this has led to many layoffs (PHK). Therefore, the participation of the community or UMKM actors in increasing creative and innovative ideas at MSMEs is very necessary so that the participation of the community can make the Indonesian economy recover. In addition, there is a need for a good strategy in planning MSMEs to help run the business. MSMEs have a very large and crucial contribution to the Indonesian economy. In the effort to increase MSMEs, there is also a need for training for the people of Pikat Village, so that people have the skills in implementing new businesses to meet their daily needs in the midst of a pandemic. Thus, this dedication is expected to be a role model for efforts to increase the development of creative and innovative MSMEs in Pikat Village, Dawan District, Klungkung Regency.